Fabrication of a Small Scale Model of Chancellor Award Trophy using CAD/CAM and CNC Milling Machine - Mohd Zain, Ihsan (Universiti teknologi petronas, 2008)
The Final Year Project (FYP) is to manufacture a small scale model of Chancellor Award Trophy using Computer Aided Design (CAD)/ Computer Aided Manufacturing (CAM) and Computer Numerical Control (CNC) milltng. The main purpose of the project is to manufacture the model by utilizing the tools and machine provided in UTP. The objectives of this project are to create 2D and 3D model (CAD) drawing of the model, to define tool path for NC codes development (CAM) and to fabricate the model using CNC milling machine (CAM). Clear and sufficient understanding of CAD/CAM process and software is needed in order to create 2D and 3D drawing thus to generate NC codes for manufacturing. The methodology involve in this project are studying and research on CAD/CAM component and familiarization on Unigraphics NX software. Next is to come up with the 2D drafting and 3D solid model drawing of the model using Unigraphics NX software. Then, overall shape and dimension of the part from the drawing will be used to define tool path to allow the Unigraphics NX software to generate the coding for CNC machining. The end results of this project are; i) 2D drafting and 3D solid model drawing, ii) Tool path, iii) NC codes, iv) Small scale model of the trophy.